The economics of airlines - Bilotkach, Volodymyr (Economics of big business., 2021)
The airline industry is fundamental to the workings of the global economy. Yet, ironically for an industry of such sheer scale and economic muscle, profit margins are razor thin and many airlines struggle to break even. The precarious economics of the sector were fully revealed when Covid-19 grounded flights across the world prompting many national carriers to seek government bailouts, while smaller airlines collapsed. In this updated and expanded new edition Volodymyr Bilotkach explains the economic realities of the airline industry and the challenges that the sector now faces after the seismic impact of the Covid-19 pandemic. The impact of such a large-scale external shock on the industry is considered across each of its sectors and for each of its primary economic determinants. The book also includes new material on changes to cost structures, the pricing of add-on services, cargo, airport slot allocation and the impact of climate change. The book remains a comprehensive introduction to the economics of airlines, how carriers compete, how they develop their business, and how demand and cost structure, coupled with the complex regulatory regime, produces the industry we see today.